INNOVATIVE APPROACHES TO ORGANIZING RESEARCH ACTIVITIES IN LITERATURE LESSONS (Multidisciplinary Journal of Science and Technology, 2026)
This article examines innovative approaches to organizing students' research activities in literature lessons within the context of modern education. The features of implementing innovative technologies aimed at developing the independence, intellectual activity, and creative potential of schoolchildren are analyzed.